Platelets generated from human embryonic stem cells are functional in vitro and in the microcirculation of living mice - Lu, Shi-Jiang (Nature Publishing Group, 2011)
Platelets play an essential role in hemostasis and atherothrombosis. Owing to their short storage time, there is constant demand for this life-saving blood component. In this study, we report that it is feasible to generate functional megakaryocytes and platelets from human embryonic stem cells (hESCs) on a large scale. Differential-interference contrast and electron microscopy analyses showed that ultrastructural and morphological features of hESC-derived platelets were indistinguishable from those of normal blood platelets. In functional assays, hESC-derived platelets responded to thrombin stimulation, formed microaggregates, and facilitated clot formation/retraction in vitro. Live cell microscopy demonstrated that hESC-platelets formed lamellipodia and filopodia in response to thrombin activation, and tethered to each other as observed in normal blood. Using real-time intravital imaging with high-speed video microscopy, we have also shown that hESC-derived platelets contribute to developing thrombi at sites of laser-induced vascular injury in mice, providing the first evidence for in vivo functionality of hESC-derived platelets. These results represent an important step toward generating an unlimited supply of platelets for transfusion. Since platelets contain no genetic material, they are ideal candidates for early clinical translation involving human pluripotent stem cells.